DEVELOPMENT TEXTBOOK WITH PROBLEM POSING METHOD TO IMPROVE SELF REGULATED LEARNING AND UNDERSTANDING CONCEPT - Eni Fariyatul Fahyuni (Pendidikan Kimia Unimus, 2019)
This research to: (1) assess textbook validity, (2) assess textbook practicality, and (3) measure textbook effectiveness to improve self regulated learning and understanding concepts in 2 Porong Junior high school. The development textbook with problem posing method refers to the Dick and Carey models. Data collected with questionnaires, observations, and pretest posttest which analyzed by t-test. The following results of textbook 3.88 (valid). The result of textbook 3.87 (practical). The results of textbooks 3.89 (effective). The textbook developed can be an alternative teaching material to support student learning